Pengaruh Live Streaming Tiktok Dan Review Pelanggan Terhadap Impulsif Buying Dan Kepuasan Pelanggan Studi Pada Konsumen Zainab Collection - Maghfiroh, Enik; Wusko, Ani Urwatul (Jurnal Administrasi Bisnis Nusantara, 2026)
This study aims to analyze the effect of live streaming and customer reviews on impulsive buying and customer satisfaction among Zainab Collection consumers. The research employs a quantitative approach with a sample of 114 respondents obtained through an online questionnaire. Data analysis was conducted using the Partial Least Square (PLS) method with the assistance of SmartPLS 4 software. The results indicate that live streaming has a positive and significant effect on impulsive buying, customer reviews have a positive and significant effect on impulsive buying, live streaming has a positive effect on customer satisfaction, customer reviews have a positive effect on customer satisfaction, and impulsive buying has a positive effect on customer satisfaction. These findings contribute to digital marketing strategies, particularly in utilizing live streaming and customer reviews to enhance consumer satisfaction